Design of cold-formed steel battened built-up columns. (June 2022) - Dar, M. Adil; Verma, Abhishek; Anbarasu, M.; Pang, Sze Dai; Dar, A.R.
Abstract: Cold-formed steel (CFS) battened columns with adequately spaced chords have structurally outperformed the conventional CFS built-up columns with closely spaced chords, but have witnessed limited research previously. The relative slenderness of the unsupported chord (between the battens) to the built-up column, is a critical parameter that governs the behavior of battened columns, and has not been appropriately addressed in previous studies, and unlike hot-rolled steel battened columns, its limiting value for a wide range of column slenderness is missing in the literature. Therefore, the various design rules proposed by different researchers for the same may not be credible. The present study focuses on the axial performance of pin ended CFS battened columns composed of two adequately spaced plain channels to form closed built-up sections. The aspect ratio of the built-up sections was fixed as unity. Finite element (FE) models were developed using ABAQUS platform, and were validated against the relevant test results available in the literature. After rigorous validation, the robust FE model developed was used to conduct an extensive parametric study by varying the vital parameters like sectional compactness of the chords, relative slenderness of the unsupported chord and overall slenderness of the battened columns. The effect of each parameter on the behavior of battened columns has been discussed extensively. Furthermore, the strengths of CFS battened columns were predicted using the current North American and European codes. It was noted that both these codes over predict the strengths of CFS battened columns, particularly when the sectional compactness of the chords is low and the relative slenderness of the unsupported chord is high. Also, a range of relative slenderness of the unsupported chord has been identified for which the prediction of the current codes is satisfactory. Based on the wide pool of data points developed, new design rules were proposed for safe and reliable predictions for CFS battened columns. The proposed design rules were verified through a reliability analysis and also the test results on CFS battened columns available in the literature. Highlights: Practical range of unsupported chord's relative slenderness ( λ chord /λ ) is studied. Behavior of stub, short, intermediate and long columns is discussed. Limiting value of λ chord /λ to prevent panel distortion is brought out. NAS/EC3 can be adopted safely if λ chord /λ ≤ 0.25. Simplified design rules are brought out for λ chord /λ ≤ 0. 50. Stub columns with λ chord /λ ≤ 0.25 exhibit superior post-peak performance.